The Extent and Pattern of Mariculture Impacts on Spatial and Seasonal Variations of Sediment Bacterial Communities Among Three Coastal Waters - Shi, Rongjun; Han, Tingting; Huang, Honghui; Kuang, Zexing; Qi, Zhanhui (Frontiers in Marine Science, 2022)
Benthic sediment bacteria are important drivers for material circulation and energy flow in aquatic ecosystem, and they are sensitive to environmental changes. Large scale suspended mariculture in coastal waters induces high organic loading to the sediment through biodeposition, and causes changes in sediment biogeochemical features. However, the impacts of mariculture on sediment bacterial communities are not fully understood. In the present study, sediment samples were collected from three coastal semi-enclosed bays of China, i.e., Sanggou Bay, Daya Bay, and Maniao Bay, where large scale mariculture were carried out since the 1980s. High-throughput sequencing was used to examine the spatial and seasonal variations of bacterial communities. The results indicated that the dominant phyla of three bays were Proteobacteria (39.18%–47.21%), Bacteroidetes (9.91%–19.25%), and Planctomycetes (7.12%–13.88%). Spatial variations played a greater role in shaping the bacterial communities than seasonal variation. The bacterial diversity indices (Chao 1, Pielou’s evenness, and Shannon-Wiener index) of Sanggou Bay were significantly lower than those of Daya Bay and Maniao Bay. For seasonal variation, bacterial diversity indices in spring were significantly lower than that in autumn. Five keystone taxa belonging to Planctomycetes, Alphaproteobacteria, and Acidobacteria were identified in Sanggou Bay. Temperature, particulate organic carbon, pH, and salinity were the most important environmental factors shaping the spatial and seasonal variations of bacterial communities in the studied areas. The abundances of bacteria, particularly Bacteroidetes, Gammaproteobacteria, and Deltaproteobacteria, were significantly correlated with the mariculture-driven chemical properties of the sediment. These results indicated that intensive mariculture could induce profound and diverse impacts on the bacterial communities, and therefore modify their role in marine ecosystem. The interactions between mariculture and sediment bacterial communities should be considered in regard to mariculture management and carrying capacity. Keywords: Mariculture; Spatial and seasonal variation; Sediment; Bacterial community; Keystone taxa